Perkembangan Teknologi Dibidang Pendidikan - Rafil Wal Ilham (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The rapid development of technology today has led to the development of the world of education and one of them is the development of learning media. Learning media is the most important factor that supports success in learning. Learning technology is an application or media that has been designed in a modern way and utilized as theory and practice in learning, as a learning resource. Currently, technology is widely used in the world of education is information technology. But also the development of technology has negative and positive impacts, which are included in the development of technology from a positive point of view, namely adding information, making the delivery of material more interesting, increasing interest in learning. With that, there is also an impact in negative terms, namely causing students to be lazy to learn, immoral violations, the emergence of deviant behavior, misuse of technology to commit criminal acts. The purpose of this research is an effort to find answers to the above problems, the development of technology in the field of education which is a very rapid and advanced development at this time especially in the learning media in the field of education. From the results of this study, the authors can conclude that the development of technology, especially in the world of education, is also stated to be very good so that students do not bore learning, especially nowadays that is increasingly sophisticated using information technology. With this, the answer to all the factors there are benefits from technological developments, namely the existence of new learning methods, facilitating access to learning can be from a distance or close distance, can also search for information using the web, improve learning abilities. Communication as an educational medium is carried out using communication media such as telephones, computers, the internet, e-mail and so on. Interaction between teachers and students is not only done through face-to-face relationships but also by using these media.